INFLUENCE OF THE TEETH NUMBER ON THE GEAR MODULE VALUE AND LOAD CAPACITY OF GEAR PAIR IN UNIVERSAL HELICAL GEAR DRIVES - Milan Rackov; Mirko Blagojević; Siniša Kuzmanović; Miloš Matejić; Ivan Knežević; Maja Čavić (Applied Engineering Letters, 2018)
The basic parameters of the universal gear drives, except the axis height, are not defined by the standard, so the manufacturers of universal gear reducers can define them in their way. Most of the manufacturers followed the parameter values of universal gear reducers of leading world producers in order to ensure their interchangeability and the better positioning of their gear units at the market. This paper deals with the analysis of the influence of the gear pair teeth number on the size of the module, as well as on the load carrying capacity of single-stage universal gear units. For defined gear ratio values, different combinations of teeth number of pinion and driven gear were selected. Further, it was made calculation of the basic geometric dimensions of the gear pair, as well as the load capacity.